Economic Policy Towards Domestic Stock Exchanges - Kowalski, Wojciech Szymon (Studia Historiae Oeconomicae, 2017)
Over the past forty years, stock exchanges have undergone a number of transformations (legal, organizational and technological). They resulted both from general external conditions (including technological progress) as well as were the expression of various economic (structural) policies. Two of which seem to be basic. The first implemented in France, based on optimal centralization of stock exchange trading. The second one, implemented in Germany and Spain, expressing the concept of a complementary and effective combination of the potentials of the main trading floor and regional exchanges. Promisingly, especially in this latter dimension of experience together with the Edinburgh ‘stock market experiment’ that has just begun, they may reveal yet another not yet fully recognized characteristic of the stock market - the institutional exemplification of the market economy.